IMPLEMENTASI MEDIASI PADA PERKARA CERAI TALAK DALAM HAL KETIDAKHADIRAN TERGUGAT DI PENGADILAN AGAMA PEKANBARU - Putri, Dinna Keumala; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
One of the peace efforts that can be done by a third party to help resolve divorce cases both in and out of court mediation, as set out in the Supreme Court Regulation No. 1 Year 2008 on Mediation Procedure in Court. In fact, the Religious Court of Pekanbaru divorce remains the most way out in the settlement of disputes between husband and wife, especially with the absence of the defendant that ultimately resulted in so many decision verstek, it means that the mediation has not been able to lower divorce rates and become effective instruments in addressing the buildup Court case. This study aims to determine the implementation of mediation applied in the Religious Court of Pekanbaru in their divorce case. This research was conducted in the Religious Court of Pekanbaru due within a period of 2 years increasing numbers verstek decision.The results showed that the implementation of mediation showed a failure rate with a variety of factors such cases, a factor the parties and the mediator factors. Implementation of mediation has not been able to lower the divorce rate and troubleshooting buildup Court case.Key Words: Implementation - Mediation - Divorce – Religious Court